Trade Costs - What Have We Learned? A Synthesis Report - Moïsé, Evdokia (OECD Trade Policy Papers, 2013)
Understanding trade costs is essential for formulating policy interventions designed to reduce such costs. This report synthesises all OECD work on cost factors across the entire trade chain. These factors can be located behind the border, such as non-tariff regulatory measures, market access restrictions, trade finance availability and costs and general impediments on doing business; crossing the border, such as documentation and customs compliance requirements, lengthy administrative procedures and other delays; and in all stages of the international trade chain, such as transport infrastructure and logistics. The report proposes a series of questions to help identify priority areas, taking into account country specificities. The strong interdependencies between cost factors, magnified by the prevalence of global value chains, mean that policies to address costs and facilitate trade need to be undertaken in a comprehensive manner, although the cost-benefit ratio of certain trade facilitation reforms, particularly at the border, may offer immediate and significant benefits